Graffiti as a sustainable development strategy for the image of urban space - Morales, Gema (Universidad Nacional de Ingeniería, 2019)
Next, the result of the research protocol based on the thesis that graffiti could be an element of sustainable development of the image of urban space from a methodological proposal that is intended to generate in the following stages of research is presented. In this context, the conceptual aspects of the urban image and urban art exposed by the most recognized theoreticians within urbanism and contemporary art are addressed. The state of the art of the same subjects is identified to be able to deduce the axes in which they have been developed and the unknowns to be solved, of which the disorder of the urban spaces where the graffiti is exhibited and the lack of valuation patterns in the modeling of it within the urban image. This allowed to structure the proposal of units of analysis, variables and their relations with the problem to be studied and thus achieve the objectives of the research.